Use of Solar Energy for Street Lighting in Rural Java - Farida Arinie Soelistianto; Harrij Mukti Khristiana (West Science Interdisciplinary Studies, 2026)
The utilization of renewable energy has become a strategic priority in supporting sustainable development, particularly in rural areas with limited access to conventional energy infrastructure. This study aims to analyze the utilization of solar energy for street lighting in rural areas of Java, focusing on community perceptions and acceptance. A quantitative research approach was employed using a structured questionnaire distributed to 85 respondents residing in villages equipped with solar-powered street lighting systems. Data were collected using a five-point Likert scale and analyzed with SPSS version 25. The analysis included descriptive statistics, reliability testing, and multiple linear regression to examine the influence of perceived effectiveness, efficiency, safety and social impact, and sustainability on community acceptance. The results indicate that all perception dimensions have a positive and statistically significant effect on acceptance of solar-powered street lighting, with perceived safety and social impact emerging as the most influential factor. Overall, the findings demonstrate that solar-powered street lighting is perceived as effective, cost-efficient, socially beneficial, and environmentally sustainable. This study provides empirical evidence to support the expansion of solar energy-based public lighting as a viable strategy for enhancing rural infrastructure and promoting sustainable energy transitions in Indonesia.